The Images of Artemis Ephesia and Greco-Roman Worship: A Reconsideration - LiDonnici, Lynn R. (Harvard theological review, 1992)
In a recent essay, Nicole Loraux identified a pattern of scholarly dependence on the origins of a particular deity for the interpretation of how human beings at various, specific times and places related to and used that figure to meet the needs of their lives. Shifting social and political conditions, such as the development and modification of the Athenian polis, led to changes in people's religious needs and are reflected by modifications, sometimes radical, in the conceptualization and worship of their gods. Loraux discussed the problems that this scholarly perspective brought to the study of goddesses in particular, where focus on the origins of many goddesses in a hypothesized worship of a Great Goddess of fertility can obscure our understanding of the ways in which these figures met the needs of individuals and cities at specific points in antiquity.